1993
DOI: 10.1029/93jb01816
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic imaging and acoustic emission monitoring of thermally induced microcracks in Lac du Bonnet granite

Abstract: Concurrent ultrasonic tomography and acoustic emission monitoring were employed to study thermally induced microfracturing in an unconfined, 15-cm cube of Lac du Bonnet granite from Atomic Energy of Canada Limited's Underground Research Laboratory. An electrical resistance cartridge heater, placed in a central vertical borehole, was used to cycle the sample to progressively higher peak temperatures between 75øC and 175øC. Tomography data were collected, at room temperature, before and after each thermal cycle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(50 citation statements)
references
References 14 publications
1
49
0
Order By: Relevance
“…DAVID et al (1999) summarized some laboratory studies that clearly showed how thermal cracking modifies elastic moduli (BARBISH and GARDNER, 1969;HEARD and PAGE, 1982;NASSERI et al, 2007), permeability (DAROT et al, 1992;MENÉNDEZ et al, 1999), and mechanical strength (HOMAND and TROALEN, 1984;HOMAND and HOUPERT, 1989). JANSEN et al (1993) investigated the development of thermal cracks by continuously monitoring the acoustic emissions (AE) generated during thermal cycles in a granite specimen. They showed that, at high temperatures, microcracks open and coalesce to form a macroscopic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…DAVID et al (1999) summarized some laboratory studies that clearly showed how thermal cracking modifies elastic moduli (BARBISH and GARDNER, 1969;HEARD and PAGE, 1982;NASSERI et al, 2007), permeability (DAROT et al, 1992;MENÉNDEZ et al, 1999), and mechanical strength (HOMAND and TROALEN, 1984;HOMAND and HOUPERT, 1989). JANSEN et al (1993) investigated the development of thermal cracks by continuously monitoring the acoustic emissions (AE) generated during thermal cycles in a granite specimen. They showed that, at high temperatures, microcracks open and coalesce to form a macroscopic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Homand-Etienne and Houpert (1989), in turn, demonstrated how the porosity of the fractures in selected rocks changes with an increase in the temperature of sample heating, and David et al (1999) analyzed the impact of temperature-induced fractures on the microstructure and selected physical properties of the La Peyratte granite. Development of thermal fractures in granite was also observed -by means of an ongoing monitoring of acoustic emission -by Calleja and Ruiz de Argandona (1984) and Jansen et al (1993). The results obtained by these researchers showed that microfractures can be observed as early as when the temperature value exceeds 80°C, and they can subsequently join together, forming structures that are macroscopic in their nature.…”
Section: Introductionmentioning
confidence: 71%
“…Using a heater placed in a central borehole, a sample of LdB pink granite was thermally cycled to progressively higher peak temperatures. Six heating cycles were performed with peak temperatures varying from 75 to 245 1C while AE data were collected; a detailed description of the experiment is given in [5,24]. The rock sample, supplied by Underground Research Laboratory (URL), Canada, was a 22 cm long cylinder, with a diameter of 30 cm and a through-going axial borehole with a diameter of 3 cm.…”
Section: Experimental Datamentioning
confidence: 99%
“…This paper describes the results of numerical simulations that were conducted in order to improve our understanding of the mechanical damage caused by thermal loading. These simulations were based on numerical models that were parameterized and validated by a previous experiment by Jansen et al [5].…”
Section: Introductionmentioning
confidence: 99%